Learning from eponyms: George F. Odland and Odland bodies - Rajiv Joshi (Wolters Kluwer Medknow Publications, 2014)
Odland bodies (lamellar) bodies are small sub-cellular structures of size 200-300 nm that are present in the upper spinous and granular cell layers of the epidermis. These act as processing and repository areas for lipids that contribute to the epidermal permeability barrier. They also contain proteases, cathepsin D, kallikrein and other proteins including corneo-desmosins. Recent information also credits them with a role in the local innate immune response as they contain beta 2 defensins, which are anti-microbial peptides with potent activity against Gram-negative bacteria and candida. Odland bodies are important for maintaining homeostasis of the epidermis and are involved in epidermal permeability barrier function, desquamation of keratinocytes, formation of the cornified envelope and in local anti-microbial immunity. This article reviews the structure and functions of these bodies with a brief biography of George F. Odland who first described these bodies in 1960 and whose name is eponymically associated with them.